Hackathons 101. - DeFranco, Joanna F.; Eagle, Christopher S.; Michael, James Bret; Viega, John; Voas, Jeffrey (Computer (00189162), 2021)
Hackathons have been around for decades. This article is a primer on what constitutes a hackathon, how hackathons have evolved, and why it can be advantageous to participate in and sponsor hackathons.